Reflection-Based CPD in Madrasah Education: A CIPP-Guided Framework for Enhancing Teacher Professionalism in Islamic School Contexts - Pahrudin, Agus; Hadiati, Eti; Thahir, Andi (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2026)
This study investigates the effectiveness of reflection-based continuous professional development (CPD) in enhancing teacher professionalism within Indonesian madrasahs. Employing an exploratory sequential mixed-methods design, this study integrates qualitative data derived from interviews, classroom observations, and document analysis with a quantitative survey encompassing 123 teachers across four madrasahs in Metro City, Lampung Province, Indonesia. The findings indicate that participation in CPD is positively associated with self-reported enhancements in pedagogical competence, professional motivation, and the adoption of innovative teaching practices. Nevertheless, the research identifies several challenges, including limited institutional support, poor alignment between CPD content and classroom requirements, and low stakeholder engagement. Statistical analysis demonstrates a significant positive correlation between CPD engagement and perceived pedagogical competence (r = 0.68, p < 0.05). Guided by the CIPP evaluation model and grounded theory, this study proposes a culturally responsive, contextspecific framework for evaluating CPD that reflects the dual religious and academic mandates inherent in madrasah education. This research contributes to the relatively underexplored discourse on professional development in Islamic educational contexts and provides actionable insights for integrating reflective practice into teacher development policies and programs.